Розвиток інформаційно-освітнього середовища сучасного закладу освіти як чинник формування професійної культури майбутніх фахівців - Євтушенко, Ганна Іванівна; Самойлова, Ірина Іванівна; Лотков, Вадим Сергійович (Університет державної фіскально служби України, 2020)
Наразі висуваються високі вимоги до професіоналізму майбутніх фахівців, до їх інформаційно-комунікаційної компетентності. Цього вимагає й сучасний вектор розвитку цивілізації, тобто спрямованість на формування інформаційного суспільства, розбудови нової інфраструктури, інтеграцію інформаційних систем і стрімку віртуалізацію оточуючої людину реальності.

Currently, there are high demands on the professionalism of future professionals, to them information and communication competence. This is required by the modern vector of civilization, ie the focus on the formation of the information society, the development of new infrastructure, the integration of information systems and the rapid virtualization of the reality surrounding man.
Development of information and educational environment of a modern educational institution as a factor in the formation of professional culture of future professionals
Keywords: розвиток; формування; професійна культура; development; formation; professional culture